Efeitos do cobre na microalga Kirchneriella obesa em cultura unialgal e em co-cultivo com Chlorella sorokiniana - Dextro, Rafael Barty (2019)
There is enough evidence that copper plays a crucial role in regulating phytoplankton metabolism. However, despite its requirement in trace amounts, there is a literature gap on the physiology of microalgae exposed to environmentally relevant copper concentrations; most literature report results using ~10 to 100 times higher copper than what can be detected in most natural ecosystems. This study aimed at investigating some physiological responses of Kirchneriella obesa exposed to copper, including environmental relevant concentrations in an ample range (3x10-9 to 4x10-5 mol L-1 free Cu2+ ions)(chapter 1) and the effects of three different copper concentrations on the co-cultivation of K. obesa and Chlorella sorokiniana (chapter 2). K. obesa’s EC50 was 1,25x10-7 mol L-1 Cu2+. Physiological analyses were performed at 72 h (exponentially growing cells) for both experiments and cultures were kept under controlled conditions. They were monitored daily for cell density, chlorophyll a and maximum photosynthetic quantum yield; biovolume and effective photosynthetic quantum yield, fluorescence quenchings (photochemical and non-photochemical) and rapid light saturation curves were also determined. In addition to these parmeters, for chapter 1, the intracellular and mucilaginous capsule copper content and total carbohydrates and proteins were determined; whereas at the end of the co-cultivation, all previously listed photosynthetic parameters were measured for each species. Intracellular and mucilaginous copper showed that the physiological mechanisms that regulate copper uptake were disrupted at 2x10-7 mol L-1 free Cu2+ ions, when intracellular copper increased linearly with copper increase in the mucilage capsule. The results showed an increase in biovolume with the increment of copper on both unialgal and co-cultures. Effective quantum yield was kept constant up to 10-7 mol L-1 Cu2+ ions but decreased thereafter. The non-photochemical quenching (NPQ) behaved the opposite way as the effective quantum yield, confirming copper induced stress in cells exposed to concentrations higher than 4x10-7 mol L-1 Cu2+ ions. Proteins and carbohydrates presented similar behaviour, increasing noticeably above 10-7 mol L-1, with higher intensity for carbohydrates. C. sorokiniana and K. obesa presented higher growth rates in the co-cultivation than in unialgal cultures when exposed to 2x10-7 mol L-1 Cu2+. This research demonstrated that environmental copper concentrations detected nowadays might affect the physiology of K. obesa and that an effect on copper toxicity may occur during the joint growth of K. obesa with C. sorokiniana. Our results are a contribution towards the understanding of the equilibrium of natural aquatic ecosystems.